2019
DOI: 10.1016/j.tig.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions Are Boring: Some Arguments about Parallel Mutations and High Mutation Rates

Abstract: Extant genomes are largely shaped by the global transposition, copy number fluctuation, and rearrangement of DNA sequences, rather than by the substitutions of single nucleotides. Although many of these large-scale mutations have low probabilities and are unlikely to repeat, others are recurrent or predictable in their effects, leading to stereotyped genome architectures and genetic variation in both eukaryotes and prokaryotes. Such recurrent, parallel mutation modes can profoundly shape the paths taken by evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 117 publications
1
39
0
Order By: Relevance
“…In comparison to single nucleotide substitutions, short tandem repeats (STRs) offer a significantly more versatile reservoir of genetic variations that may be necessary for speciation and species-specific phenotypes [1,2]. We have previously reported that approximately 2% of the human protein-coding genes contain STRs of ≥6 repeats in the critical core promoter region [3].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to single nucleotide substitutions, short tandem repeats (STRs) offer a significantly more versatile reservoir of genetic variations that may be necessary for speciation and species-specific phenotypes [1,2]. We have previously reported that approximately 2% of the human protein-coding genes contain STRs of ≥6 repeats in the critical core promoter region [3].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it will be important to reveal if these variants show functional variability in these genes. Recently, the importance of variation sources resulting in the occurrence of parallel mutations has been highlighted [56].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the fact that, while not frequently measured or modeled, rates of mutation other than base substitution rates are critical to quantify and understand, as they may be much greater sources of genetic variation, both in terms of frequency and the size of the mutations that occur, than the simple substitution of one nucleotide for another (Press et al 2019). While bsMRs will likely remain the most commonly measured mutation rate, our prediction that there would be little to no correlation between those rate estimates with TE mutation rates bore out ( Figure 4A and B), even though they do positively correlate with microsatellite rates (Ho et al 2020).…”
Section: Correlations With Te Mutation Ratesmentioning
confidence: 99%